The impact of hypertensive disorders of pregnancy on maternal and perinatal outcomes in Ethiopia: an umbrella review of systematic reviews - Teketel Ermias Geltore; Simegn Alemu; Tariku Laelago Ersado; Tamiru Beyene Uliso; Abebe Alemu Anshebo; Lakew Lafebo Foto (Frontiers in Global Women's Health, 2025)
BackgroundPrevious systematic reviews and meta-analyses have concentrated on the impacts of hypertensive disorders of pregnancy on maternal and perinatal outcomes in Ethiopia. Still, the evidence has often been inconsistent and inconclusive. Consequently, this study seeks to consolidate the findings regarding the effects of hypertensive disorders during pregnancy on maternal and perinatal outcomes in Ethiopia.MethodsPubMed, Science Direct, Google Scholar, Africa Journal Online, PsycINFO, Research4Life, and CINAHL from September 15 to 25, 2024. The quality of the methods was assessed using the Assessment of Multiple Systematic Reviews (AMSTAR) tool. The estimates from the included studies were pooled and summarized using random-effects meta-analysis models.ResultsWe included five systematic reviews and meta-analyses (SRM) studies with a total of 621,146 pregnant women. The pooled prevalence of hypertensive disorders of pregnancy was 16.56% (95% CI: 13.15–20.02), with a heterogeneity index (I2 = 94.17%, P = 0.00). Maternal age >35 years, (AOR = 2.29; 95% CI: 2.05, 2.94), previous history of preeclampsia, (AOR = 3.51; 95% CI: 2.26, 5.53), low birth weight (AOR = 2.18; 95% CI: 1.48, 3.01), and alcohol consumption (AOR = 1.84; 95% CI: 1.12, 2.46) were the risk factors and complications of hypertensive disorders of pregnancy.ConclusionThe higher rate of severe forms of HDP that are associated with significant maternal and perinatal complications is a major concern in Ethiopia. The risk of developing HDP is worse among women who have a history of preeclampsia, maternal age >35 years, alcohol consumption, and its complications, such as low birth weight.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024578548.